A Comparative Cost Analysis of Local Anesthesia versus Brachial Plexus Block for Complex Hand Surgery. (January 2023) - Baradaran, Aslan; Meng, Fanyi; Jaberi, Mehrad Mojtahed; Finlayson, Roderick; Thibaudeau, Stephanie
Background: Local anesthesia has shown to be safe and cost-effective for elective hand surgery procedures performed outside of the operating room. The economic benefits of local anesthesia compared to regional anesthesia for hand surgeries performed in the operating room involving repair of tendons, nerves, arteries, or bones are unclear. This study aimed to compare costs pertinent to hand surgeries performed in the main operating room under local anesthesia (LA) or brachial plexus (BP) block. Methods: We performed a cross-sectional study on the first 70 randomized patients from a prospective controlled trial of anesthesia modalities for hand surgery. The primary objective was to determine the mean anesthesia-related cost, and the secondary objectives were to analyze block performance time, block onset time, duration of anesthesia, duration of surgery, and time in the recovery room. Results: The mean anesthesia-related cost of performing hand surgery under LA as a wrist and/or digital block was 236 ± 30, compared to 435 ± 43 for BP, a difference of 199 per case. The mean block performance time was shorter for LA (1.3 minutes) versus BP (7.0 minutes). The mean anesthesia-related time was longer in BP (30.7 ± 16 minutes) compared to LA (17.7 ± 6.7 minutes), and consequently the total anesthesia time was longer in BP. Conclusions: We demonstrated that local anesthesia compared to brachial plexus block achieved substantial cost savings in complex hand surgeries by decreasing major expenses. In an era of cost-consciousness, the use of LA represents an important modality for health systems to optimize patient flow and increase cost-effectiveness.